Root development impacts on the distribution of phosphatase activity: Improvements in quantification using soil zymography. (January 2018) - Giles, C.D.; Dupuy, L.; Boitt, G.; Brown, L.K.; Condron, L.M.; Darch, T.; Blackwell, M.S.A.; Menezes-Blackburn, D.; Shand, C.A.; Stutter, M.I.; Lumsdon, D.G.; Wendler, R.; et al.
Abstract: Zymographic methods for the 2D distribution of phosphatase activity in soils have markedly advanced our understanding of root-soil-microbiota interactions. Robust quantitative approaches for 2D assays, which use 4-methylubelliferyl phosphate (4-MUP), are needed to advance a mechanistic understanding of enzyme behaviour and distribution in soils. We present improvements to the method for phosphatase zymography in rhizobox studies, involving (1) a systematic evaluation of 4-methylumbelliferone (4-MU)-based calibration functions in relation to image exposure time and (2) the development of advanced image analysis tools for lateral and longitudinal distributions of phosphatase activity along barley roots ( Hordeum vulgare L., cv Optic). Exposure time (<1–32 s) affected the slope and intercept of 4-MU calibration equations by 4.4- and 5.8-fold, respectively. In lateral root profiles, a linear relationship was found between phosphatase activity and root hair length at 0 cm (7 nKat mm -2 ), 0.2 cm (48 nKat mm −2 ), and 2 cm (234 nKat mm −2 ) distance from the root tips (r = 0.9795, p < 0.0001); an algorithm designed to optimise estimates of phosphatase activity longitudinally confirmed this relationship (r = 0.9462, p < 0.0001). To improve the precision and accuracy of fluorescence-based soil zymography, careful control of calibration and imaging conditions and further development of advanced image analysis techniques are recommended. Highlights: Calibration and image analysis pipeline for soil phosphatase zymography. Exposure time impacts on precision and accuracy of phosphatase activity measurements. Acid phosphatase activity related to root hair length along barley roots in soil.